Autism? Aspergers? ADHD? ADD? : a parent's roadmap to understanding and support! - Burns, Diane Drake. 4 0 16; 5 (Arlington, Texas : Future Horizons, 2005)
A guide to navigating the early stages of your child's life when you know something is different and a diagnosis is hard to come by.
Includes bibliographical references.
Adult.
Keywords: 2 -- 0; 6; Autism.;Asperger's syndrome.;Attention-deficit hyperactivity disorder.;Attention-deficit-disordered children.;Attention deficit disorder; 20; 2